2020
DOI: 10.1186/s41610-020-00160-z
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of the Korean wild boar Sus scrofa coreanus (Suidae) at Mt. Jeombongsan, Korea

Abstract: Background Korean wild boars (Sus scrofa coreanus Heude), because of their adaptability, are a widespread large mammal; however, they sometimes cause problems by invading farms and eating the crops, creating insufficiencies of some foods in South Korea. To understand the diet composition of Korean wild boars according to sex and body size, we collected their feces from Mt. Jeombongsan, Seoraksan National Park, South Korea. The sizes of fecal samples were measured, and genomic DNA was extracted from the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…S. scrofa is considered a pest in many countries due to its feeding activities, it damages crops and could affect native communities (Ballari et al, 2014;Barrios-Garcia & Ballari, 2012;Cuevas et al, 2010;Shin et al, 2020). Its diet consists of belowground part of plants, mainly roots and bulbs and fleshy fruit and aboveground green plant material as well as worms (Baubet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…S. scrofa is considered a pest in many countries due to its feeding activities, it damages crops and could affect native communities (Ballari et al, 2014;Barrios-Garcia & Ballari, 2012;Cuevas et al, 2010;Shin et al, 2020). Its diet consists of belowground part of plants, mainly roots and bulbs and fleshy fruit and aboveground green plant material as well as worms (Baubet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Angom et al., 2020 ; Modi et al., 2021 ; Ramón‐Laca et al., 2015 ), and this protocol's extraction method has also been separately used in studies on species diet (e.g. Bhattacharyya et al., 2019 ; Galan et al., 2018 ; Guo et al., 2018 ; Shin et al., 2020 ). Protocol B (Qiagen Mobio Powersoil Kit, part of Protocol B) has been extensively used for recovering environmental DNA for dietary analysis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has also continued in the majority of recent molecular scatology studies that have started to combine questions on the target species itself (gene flow, inbreeding, sex ratio and dispersal patterns) with questions regarding their diet (e.g. Abdullah‐Fauzi et al., 2022 ; Bison et al., 2015 ; Buglione et al., 2018 ; Jesmer et al., 2020 ; Shi et al., 2021 ; Shin et al., 2020 ) although a recent study has demonstrated utilities of one single protocol (de Flamming et al., 2023). The collection, processing and extraction of faecal samples for target species studies often revolve around collecting samples and storing them in either −20°C conditions or in a storage medium such as ethanol, silica beads or RNAlater solution, followed by swabbing/scraping off the outer layer and extracting DNA using stool kit‐based methods/CTAB method/phenol‐chloroform (Ball et al., 2007 ; Biswas et al., 2019 ; Paul et al., 2019 ; Ramón‐Laca et al., 2015 ; Waits & Paetkau, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation